Activation of a Drosophila Janus kinase (JAK) causes hematopoietic neoplasia and developmental defects. - Harrison, D.A.; Binari, R.; Nahreini, T.S.; Gilman, M.; Perrimon, N. (The EMBO Journal, 1995)
In mammals, many cytokines and growth factors stimulate members of the Janus kinase (JAK) family to transduce signals for the proliferation and differentiation of various cell types, particularly in hematopoietic lineages. Mutations in the Drosophila hopscotch (hop) gene, which encodes a JAK, also cause proliferative defects. Loss-of-function alleles result in lethality and underproliferation of diploid tissues of the larva. A dominant gain-of-function allele, Tumorous-lethal (hopTum-l), leads to formation of melanotic tumors and hypertrophy of the larval lymph glands, the hematopoietic organs. We show that a single amino acid change in Hop is associated with the hopTum-l mutation. Overexpression of either wild-type hop or hopTum-l in the larval lymph glands causes melanotic tumors and lymph gland hypertrophy indistinguishable from the original hopTum-l mutation. In addition, overexpression of Hop in other tissues of the larva leads to pattern defects in the adult or to lethality. Finally, overexpression of either hop or hopTum-l in Drosophila cell culture results in tyrosine phosphorylation of Hop protein. However, overexpression of hopTum-l results in greater phosphorylation than overexpression of the wild-type. We conclude that hopTum-l encodes a hyperactive Hop kinase and that overactivity of Hop in lymph glands causes malignant neoplasia of Drosophila blood cells.